Symphony no. 3 "Eroica" - Beethoven, Ludwig van 1770-1827.; Kegel, Herbert; Dresdner Philharmonie (Santa Monica, CA LaserLight, 1995)
Computer readable information includes biographies, historical information, and scores.
CD+ROM data track -- Audio tracks.
"Version: 1.0."
Compact disc.
Dresden Philharmonic; Herbert Kegel, conductor.
System requirements for use as a computer disc: IBM 486 or compatible PC; Windows 3.1.
Keywords: Beethoven, Ludwig van -- 1770-1827.; Symphonies